(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Miguel Street is a novel by V.S. Naipaul, focusing on the struggle for identity in postcolonial Trinidad. The novel follows seventeen characters from diverse cultural backgrounds, grappling with colonialism’s legacy and cultural displacement.